Investigating Consumer S Sophistication, Cynicism And Efficacy On Emotion-Based Political Brand Equity Using Anes Panel Data : Moderating Role Of Partisanship - Almohammad, Asaad Hasan (2017)
Utilising secondary data from American National Election Studies, namely the 2008-2009 panel study, this research aims to test the direct and indirect relationships between consumer‘s political sophistication and emotion-based political brand equity, and thereby emotion-based political brand equity predictive power of consumer‘s voting choice. Grounded on the positive paradigm, this thesis utilises a quantitative methodology, namely, descriptive, in testing the aforementioned premises. The findings of this thesis suggest that consumer‘s sophistication, cynicism and efficacy are related to emotion-based PBE; consumer‘s partisanship alters the positive relationship between consumer‘s sophistication.